A dosimetric study of cardiac dose sparing using the reverse semi-decubitus technique for left breast and internal mammary chain irradiation. Issue 1 (January 2016) - Niglas, Mark; McCann, Claire; Keller, Brian M.; Makhani, Nadiya; Presutti, Joseph; Vesprini, Danny; Rakovitch, Eileen; Elzibak, Alyaa; Mashouf, Shahram; Lee, Justin
Abstract: Background and purpose: Breath-hold techniques can reduce cardiac dose in breast radiotherapy. The reverse semi-decubitus (RSD) technique is an alternative free-breathing method used at our centre. This study compares the dosimetry of free-breathing supine, RSD and moderate deep inspiration breath-hold (mDIBH) techniques. Materials and methods: Twelve patients with left-sided breast cancer who were simulated using standard supine, RSD and mDIBH techniques were identified retrospectively. New plans using standard breast tangents and techniques for internal mammary chain (IMC) nodal coverage were assessed. Results: Using standard tangents, mean heart dose, heart V 25Gy and mean left anterior descending artery (LAD) dose were found to be significantly lower for RSD and mDIBH when compared to free-breathing supine ( p ⩽ 0.03). Using wide-tangents, the maximum LAD point dose was also lower for RSD and mDIBH ( p ⩽ 0.02). There were no statistically significant dosimetric differences found between the RSD and mDIBH simulation techniques for standard breast-tangent plans, though organ-at-risk doses were lower for mDIBH in wide-tangent plans. There was no improvement in cardiac dosimetry between RSD and free-breathing supine when using an electron field IMC plan. Conclusions: For patients unable to tolerate breath-hold, the RSD technique is an alternative approach that can reduce cardiac dose.